Pengaruh Laba Per Saham (Earning Per Share) dan Nilai Buku Per Saham (Book Value Per Share) terhadap Harga Saham pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Miranti, Miranti; Naiggolan, Karlonta; Situmorang, Halomoan (Economics, Business and Management Science Journal, 2024)
The capital market is a means where long-term securities are bought and sold. Every company that is listed on the Indonesian Stock Exchange or goes public must issue shares that can be owned by every investor. Many factors can influence share prices such as Earning Per Share and Book Value Per Share. This research aims to determine the influence of Earning Per Share and Book Value Per Share on share prices, either partially or simultaneously. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange. The type of research used by the author is associative research, the population in this research is manufacturing companies listed on the Indonesia Stock Exchange for the 2012-2014 period, totaling 134 companies. Using several criteria determined by the author, a sample of 20 companies was obtained multiplied by three years to become 60 financial report data and the sampling technique was carried out using purposive sampling. The type of data in this research is quantitative data. The analysis technique used is multiple regression. The results of analysis using multiple regression show that Earning Per Share has an effect on share prices. Meanwhile, Book Value Per Share has no effect on share prices. Simultaneously, Earning Per Share and Book Value Per Share influence share prices.